Inovação na gestão pública do Espírito Santo : um estudo do prêmio Inoves - Costa, Betânia de Laia (2015)
The aim of this study is to analyze the INOVES award as an effective tool for the innovative initiatives in public administration in the State of Espírito Santo, according to actors directly involved with the award. Therefore, the idea of innovation has a